Exploring the implementation of multidisciplinary collaboration at nursing homes in Jakarta, Indonesia: A descriptive phenomenological study - Royani; Hamid, Achir Yani S.; Rekawati, Etty; Darmawan, Ede Surya (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: A well-functioning multidisciplinary team optimizes resource utilization and reduces care redundancy, fragmentation, and wastage. Collaborative efforts yield a clearer understanding of older people’s needs and desires, significantly reducing hospitalization days. Despite limited studies, particularly in Indonesia, investigating professionals’ experiences in implementing multidisciplinary collaboration in government nursing homes, nursing care quality remains a concern. Objective: This study aimed to explore the implementation of multidisciplinary collaboration in nursing homes from the perspectives of various disciplines. Methods: A descriptive phenomenological study was used with semi-structured interviews and focus group discussions with multidisciplinary care providers, including nurses, doctors, social workers, physiotherapists, psychologists, occupational and recreational activity instructors, and clergy in nursing homes owned by the Jakarta provincial government. A total of 64 participants were involved, and data were collected from September 2022 to July 2023. Data were analyzed using content-based analysis. Results: Three main themes emerged: 1) context of multiple collaborations, 2) barriers to implementing multiple collaborations, and 3) impacts of non-optimal multidisciplinary collaborations. Nursing home management’s multidisciplinary teams predominantly implement professional-centered care with limited support systems. While providers generally perceive collaboration positively, shared responsibility and joint work among professionals are lacking. Conclusion: This study highlights the need to improve multidisciplinary collaboration in nursing homes to enhance care quality for older individuals. While providers view collaboration positively, barriers like a lack of shared responsibility and joint work persist. Enhancing teamwork cohesion through improved communication and integrated case reporting systems is crucial. Addressing human resource and systemic barriers is also vital. By overcoming these challenges, nursing homes can optimize resource use, reduce care redundancy, and better meet the diverse needs of older residents.